1977
DOI: 10.1002/cne.901740307
|View full text |Cite
|
Sign up to set email alerts
|

Some visual and other connections to the cerebellum of the pigeon

Abstract: By anatomical techniques it has been shown that folia VIc-IXc of the pigeon cerebellum receive inputs from the following groups of neurons: the medial and lateral pontine nuclei, the superficial synencephalic nucleus, the medial spiriform nucleus, the inferior olive, and the deep cerebellar nuclei. From all but the last of these, the projection is mainly crossed, though the uncrossed component from the lateral pontine nucleus is not insubstantial. The input from the superficial synencephalic nucleus provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
118
2
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 27 publications
15
118
2
2
Order By: Relevance
“…Based upon the analyses presented in mammals, any significant correlations are likely to be between those regions sharing the greatest interconnectivity (Barton & Harvey 2000). Specifically, we expected significant correlations between five region pairs because of the large number of connections that they share with one another: telencephalon and diencephalon; diencephalon and mesencephalon; mesencephalon and optic tectum; mesencephalon and myelencephalon; and myelencephalon and cerebellum (Clarke 1977;Bravo & Pettigrew 1981;Arends & Zeigler 1991;Wild et al 1993;Wild 1997;Husband & Shimizu 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Based upon the analyses presented in mammals, any significant correlations are likely to be between those regions sharing the greatest interconnectivity (Barton & Harvey 2000). Specifically, we expected significant correlations between five region pairs because of the large number of connections that they share with one another: telencephalon and diencephalon; diencephalon and mesencephalon; mesencephalon and optic tectum; mesencephalon and myelencephalon; and myelencephalon and cerebellum (Clarke 1977;Bravo & Pettigrew 1981;Arends & Zeigler 1991;Wild et al 1993;Wild 1997;Husband & Shimizu 2002).…”
Section: Introductionmentioning
confidence: 97%
“…12,19,20 Nuclei of the accessory optic system project to areas of the inferior olive (IO) that provide climbing fiber input to the contralateral vestibulocerebellum (VbC). 1,[6][7][8]20,33 In pigeons, the VbC consists of folium X (nodulus), the ventral lamella of folium IXc,d (ventral uvula) and the auricle (flocculus), which is the lateral extension of these folia. 18 Previous electrophysiological studies of the pigeon VbC have shown that complex-spike (CS) activity of Purkinje cells (which reflects climbing fiber activity) responds best to specific patterns of optic flow resulting from either self-translation or self-rotation.…”
mentioning
confidence: 99%
“…In some birds, the HRP-positive neurons were also present in the nucleus of posterior commissure (Jungherr, 1969). The distribution pattern of the labeled neurons in midbrain and diencephalon was similar to the pigeon (Clarke, 1977).…”
Section: Injection Of Hrp Into Folia Vi-viii Of the Cerebellum In Youmentioning
confidence: 65%
“…In the pons, the labeled neurons existed mainly in the pontine nuclei, and the locus ceruleus. In the midbrain and diencephalon, the HRP-positive cells were located in the red nucleus, the superfiscial synencephalic nucleus (Clarke, 1977), the medial spiriform nucleus, the nucleus ectomamillaris (Brecha et al, 1980) and the ventral part of the lateral geniculate nucleus (Clarke, 1977;Fig. 2).…”
Section: Injection Of Hrp Into Folia Vi-viii Of the Cerebellum In Youmentioning
confidence: 99%
See 1 more Smart Citation